Antecedent Factors of Well-Being in the World's Muslim Population: A Systematic Literature Review - Aditya Aryo Nur Kusumo; Fadhilah Suralaga; Rena Latifa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Most studies on well-being have been conducted in Western countries dominated by secular and individualistic values, thus not fully representing the experiences of Muslims who have different cultural backgrounds and religious values. This study aims to systematically synthesize various studies on well-being in Muslim populations to formulate antecedent factors that influence Muslim well-being. Using a Systematic Literature Review (SLR) approach, 59 scientific articles published between 2006 and 2023 were analyzed using an inductive content analysis method. The results of the synthesis indicate that seven main factors influence well-being in Muslim societies: (1) orientation to the afterlife, (2) harmony of cultural and religious values, (3) theological perspective, (4) ritual worship practices, (5) gratitude, (6) religiosity and spirituality, and (7) hope. These seven factors form a conceptual framework that is sensitive to the Islamic cultural and religious context. This study makes a novel contribution by offering a multidimensional model of well-being integrated with faith values. The theoretical and practical implications of this study include the need to create mental health interventions and well-being measurement tools that are appropriate to the context of Muslim communities. The results also emphasize the importance of educating mental health professionals to be more sensitive to religious and cultural differences.